2004
DOI: 10.1063/1.1633343
|View full text |Cite
|
Sign up to set email alerts
|

Annealing effect on the property of ultraviolet and green emissions of ZnO thin films

Abstract: A differential (or balanced) bandpass filter based on open complementary split ring resonators (OCSRRs) coupled through admittance inverters is presented in this article. Pairs of OCSRRs are symmetrically placed in a mirror configuration between the strips of the differential line and are modeled by means of two series connected parallel resonators. For the differential (odd) mode, there is a virtual ground at the connecting plane between the OCSRR pairs, and the structure is roughly described by the canonical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
156
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 561 publications
(177 citation statements)
references
References 34 publications
17
156
0
4
Order By: Relevance
“…Interestingly, a new band at 405 nm emerged in the ZnO NSs annealed at or above 800°C, which was due to the formation of Zn 2 SiO 4 composites. 30 This band became stronger as the annealing temperature increased, as observed in the XRD results and previously discussed. The DBE band was also fitted with the Gaussian function to find the total integrated intensity of the band.…”
Section: Pl Spectroscopysupporting
confidence: 70%
“…Interestingly, a new band at 405 nm emerged in the ZnO NSs annealed at or above 800°C, which was due to the formation of Zn 2 SiO 4 composites. 30 This band became stronger as the annealing temperature increased, as observed in the XRD results and previously discussed. The DBE band was also fitted with the Gaussian function to find the total integrated intensity of the band.…”
Section: Pl Spectroscopysupporting
confidence: 70%
“…The broadening of violet-blue emission peak could be attributed to hybridization of various defect states induced by the non-equilibrium ball milling method of preparation and size distribution. In addition, a much weaker peak is located at 550 nm which is attributed to the surface defects from oxygen vacancies or Zn i [23]. Vanheusden et al [24] found that oxygen vacancies are responsible for the green luminescence in ZnO.…”
Section: Resultsmentioning
confidence: 99%
“…The broad peak around 2.471 eV in the blue-green region is related to complex defect species, which is usually attributed to zinc interstitial or oxygen vacancies. 19 The peak in the ultraviolet region is related to excitonic emission. It can be seen that the tetrapods exhibited much lower defect state emissions than the multipods.…”
Section: Resultsmentioning
confidence: 99%